Soil-Cement Matrices for Additive Construction: 3D printing System Validation and Printing Tests - Silva, G.; Burgos, V.; Ñañez, R.; Kim, S.; Ruiz, G.; Pando, M.A.; Aguilar, R.; Nakamatsu, J. (Trans Tech Publications Ltd, 2023)
Soil as a building material is gaining renewed interest from academia, and the construction sector, mainly for fabricating low-environmental impact homes. The fabrication of houses with soil using traditional methods such as adobe, cob, and rammed earth dates back to ancient times. However, emerging construction technologies, such as 3D printing, can be compatible with this material for building purposes. The article presents the validation of a 3D printing system for construction applications and the evaluation of soil-cement matrices' printability. First, the paper defines the printing parameters through experimental testing on soil matrices. Then, the article evaluates the printability of soil-cement matrices through filament printing and stacking tests. The results show that the 3D printing system prototype can fabricate small and medium-sized elements with soil matrices after correctly defining the pumping speed, printing speed, and layer height. Furthermore, experimental printing test results demonstrate that soil-cement matrices can be easily extruded and stacked; however, their printability capacity is strongly affected by the total water content and printing speed. This research highlights the suitability of soil-cement mixtures for additive manufacturing, a promising outcome that can facilitate the construction of homes in remote areas using 3D printing systems.
Keywords: 3D printing; Cement; Soil cement; Adobe; Materials science; Masonry; Fabrication; Mechanical engineering; Civil engineering; Engineering; Composite material; https://purl.org/pe-repo/ocde/ford#2.01.04